UP TO DATE APPROACHES TO IMPROVING IMMUNOBIOLOGICAL THERAPY OF VIRAL DIARRHEA OF CHILDREN - L.N. Mazankova; T.A. Chebotareva; I.D. Maikova (Педиатрическая фармакология)
The article considers issues of therapeutic tactics for virus infections of children. The authors explain the essence of changes, which take place in the immune system of body under this pathology. The article describes immuno pathogenesis of acute enteric infections and the effect of lactoprobiotics on immuno-competent cells. The findings prove the advisability of applying this group of medications for a complex therapy of children with acute diarrhea disturbance.Key words: acute enteric infections, immuno-pathogenesis, treatment, lacto probiotics, children.